2016
DOI: 10.1159/000453180
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of IhERG/IKr Modulation by α1-Adrenoceptors in HEK293 Cells and Cardiac Myocytes

Abstract: Background: The rapid delayed rectifier K+ current (IKr), carried by the hERG protein, is one of the main repolarising currents in the human heart and a reduction of this current increases the risk of ventricular fibrillation. α1-adrenoceptors (α1-AR) activation reduces IKr but, despite the clear relationship between an increase in the sympathetic tone and arrhythmias, the mechanisms underlying the α1-AR regulation of the hERG channel are controversial. Thus, we aimed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…Moreover, we found that A61603 produced a similar effect to the cPKC‐specific activator peptide. The results are consistent with the previous reports that PKC activators or phenylephrine cause a depolarizing shift in the voltage‐dependent activation of the hERG channels (Thomas et al, , ; Urrutia et al, ). Western blot analysis showed that the phospho‐PKCα, but not phospho‐PKCε, was increased in the ventricular myocytes after α 1A ‐adrenoreceptor stimulation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, we found that A61603 produced a similar effect to the cPKC‐specific activator peptide. The results are consistent with the previous reports that PKC activators or phenylephrine cause a depolarizing shift in the voltage‐dependent activation of the hERG channels (Thomas et al, , ; Urrutia et al, ). Western blot analysis showed that the phospho‐PKCα, but not phospho‐PKCε, was increased in the ventricular myocytes after α 1A ‐adrenoreceptor stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous study has shown that stimulation of AT 1 receptors produces an acute inhibitory effect on I Kr /hERG currents via a PKC pathway in guinea pig ventricular myocytes and HEK293 cells (Wang et al, ). Meanwhile, activation of α 1A ‐adrenoceptors also results in an instant inhibition of I Kr /hERG current through PKC signalling (Thomas et al, ; Urrutia et al, ). Accordingly, hERG channels represent a target for modulation by autonomic neurotransmitters and hormones, and thus, PKC may become a candidate mediator of the pathological cardiac electrophysiological remodelling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also confirm a role of the N-terminal part of the protein as proposed by other studies [11,34]. Cockerill and coworkers found that residues 2-354 of the K V 11.1 N-terminus are critical for both cPKC phosphorylation and functional modulation of the channel [11].…”
Section: Functional Analysis Of K V 111 Mutants Supports S284 As Possupporting
confidence: 80%
“…The pharmacological and biophysical properties of I K(erg) in GH 3 cells were previously described [19]. Physiological roles of I K(erg) in different types of cells have been also reported [20,21]. However, at the level of -100 mV, the peak amplitude of deactivating I K(erg) did not differ significantly between the absence and presence of 10 μM ART (787 ± 14 pA [control] versus 782 ± 13 pA [in the presence of ART], n = 7, P > 0.05).…”
Section: Inhibitory Effect Of Art On I K(dr) In Gh 3 Cellsmentioning
confidence: 99%